Implementasi Kebijakan Wajib Serap Gabah Tanpa Standar Kualitas Oleh Perum BULOG Lampung - Alya Adila; Susana Indriyati Caturiani; Nana Mulyana (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2026)
Presidential Instruction Number 6 of 2025 on the Procurement and Management of Domestic Rice Paddy/Rice and the Distribution of Government Rice Reserves serves as the legal basis for the mandatory rice paddy absorption policy without quality standards as an effort to protect farmers and maintain rice price stability. Perum BULOG is appointed as the main implementing agency of this policy. However, several implementation issues have emerged at the field level, including limited human and logistical resources, high administrative burdens, delays in payment, and uneven understanding of the policy among farmers. This study aims to analyze the implementation of the mandatory rice paddy absorption policy without quality standards by Perum BULOG in Lampung Province and to identify the supporting and inhibiting factors affecting its implementation. This research employs a qualitative approach, with data collected through interviews, observation, and documentation. The findings indicate that policy implementation is supported by cross-sectoral communication and coordination, implementers’ commitment, and a clear organizational structure within BULOG. The policy has contributed to increased rice paddy absorption and price stability at the farmer level. However, its effectiveness has not yet been optimal due to resource constraints, rigid bureaucratic procedures, and technical challenges in field operations. From the perspective of Edward III’s policy implementation theory, the policy has fulfilled the aspects of communication and implementers’ disposition but still requires strengthening in terms of resources and bureaucratic flexibility to achieve its objectives more effectively.